Labor-Market Scars When Youth Unemployment Is Extremely High: Evidence from Macedonia - Marjan Petreski; Nikica Mojsoska-Blazevski; Marcelo Bergolo (Institute for the Study of Labor (IZA), 2016)
The objective of this study is to assess how the duration of the unemployment spell of Macedonia youth affects later employment (the employment 'scarring' effect) and wage outcomes (the wage 'scarring' effect). To that end, we first devise a model in which the unemployment spell is determined by individual and household characteristics and work attitudes and preferences. Discrete-time duration method is used to estimate this model. Then, we rely on a standard employment and Mincer earnings functions. We repeatedly impute missing wages to address the selection on observables, and use the regional unemployment rate when individual finished school as an instrument to mitigate the selection on unobservables. The School to Work Transition Survey 2012 is used. Results robustly suggest a presence of employment scar as those young persons who stay unemployed over a longer period of time were found to have lower chances to find a job afterwards. On the other hand, the study does not provide evidence for the existence of the wage scar.
Keywords: E24; J24; J64; 330; employment scarring; wage scarring; extremely high unemployment; Macedonia